Movement Sonification in Stroke Rehabilitation - Schmitz, Gerd; Bergmann, Jeannine; Effenberg, Alfred O.; Krewer, Carmen; Hwang, Tong-Hun; Müller, Friedemann (Frontiers in Neurology, 2018)
Stroke often affects arm functions and thus impairs patients’ daily activities. Recently, several studies have shown that additional movement acoustics can enhance motor perception and motor control. Therefore, a new method has been developed that allows providing auditory feedback about arm movement trajectories in real-time for motor rehabilitation after stroke. The present article describes the study protocol for a randomized, controlled, examiner and patient blinded superiority trial (German Clinical Trials Register, www.drks.de, DRKS00011419), in which the method will be applied to 13 subacute stroke patients with hemiparesis during 12 sessions of 30 minutes each as additional feedback during the regular movement therapy. As primary outcome, a significant pre-post-change in the Box and Block Test is expected that exceeds the performance increase of 13 patients who will be provided with sham-acoustics. Possible limitations of the method as well as the study design are discussed.